Measuring monetary policy stance in Brazil - Brisne J. V. Céspedes; Elcyon Caiado Rocha Lima; Alexis Maka; Mário Jorge Cardoso de Mendonça (Institute for Applied Economic Research (ipea), 2015)
In this article we use the theory of conditional forecasts to develop a new Monetary Conditions Index (MCI) for Brazil and compare it to the ones constructed using the methodologies suggested by Bernanke and Mihov (1998) and Batini and Turnbull (2002). We use Sims and Zha (1999) and Waggoner and Zha (1999) approaches to develop and compute Bayesian error bands for the MCIs. The new indicator we develop is called the Conditional Monetary Conditions Index (CMCI) and is constructed using, alternatively, Structural Vector Autoregressions (SVARs) and Forward-Looking (FL) models. The CMCI is the forecasted output gap, conditioned on observed values of the nominal interest rate (the Selic rate) and of the real exchange rate. We show that the CMCI, when compared to the MCI developed by Batini and Turnbull (2002), is a better measure of monetary policy stance because it takes into account the endogeneity of variables involved in the analysis. The CMCI and the Bernanke and Mihov MCI (BMCI), despite conceptual differences, show similarities in their chronology of the stance of monetary policy in Brazil. The CMCI is a smoother version of the BMCI, possibly because the impact of changes in the observed values of the Selic rate is partially compensated by changes in the value of the real exchange rate. The Brazilian monetary policy, in the 2000:9- 2005:4 period and according to the last two indicators, has been expansionary near election months.
Keywords: E52; E58; 330